The Effect of High-Dose Intravenous N-Acetylcysteine Administration on Tumor Necrosis Factor-α (TNF) - Sahrun Sahrun (GLOBAL HEALTH SCIENCE GROUP, 2024)
Respiratory tract infections are among the five most common health problems worldwide, with pneumonia being a significant contributor. Pneumonia continuously increases the rates of morbidity and mortality globally. Pneumonia is classified into three categories, one of which is Community Acquired Pneumonia (CAP). The incidence of community-acquired pneumonia increases with age. The risk of death from pneumonia also increases in individuals over 65 years old and those with comorbidities.The objective of this study is to assess the impact of high-dose intravenous N-acetylcysteine on the clinical improvement of inflammatory markers (TNF-α) among hospitalized CAP patients with comorbidities.Methods: This study is a randomized controlled trial. The sample population comprises patients with respiratory diseases hospitalized at RS Patut Patuh Patju (Tripat) Gerung. The sample size was obtained through total sampling during the period from January to May 2022, ranging from 10 to 25 patients per month, with an average of 15 patients per month. The dependent variable in this study is CAP with comorbidities, while the independent variable is the clinical improvement of inflammatory markers. Data analysis between variables was performed using a t-test for two means. The aim of this study is to assess the effect of clinical improvement in inflammatory markers (TNF-α) in hospitalized CAP patients with comorbidities after the administration of high-dose intravenous N Acetylcysteine. The mean value of Tumor Necrosis Factor-α before the intervention was 77.699, and the post-test mean value was 41.137. The analysis of the paired t-test for Tumor Necrosis Factor-α showed a P value of 0.000 <α=0.05. The Mann-Whitney test used to assess the difference in Tumor Necrosis Factor-α between the Intervention and control groups after N-Acetylcysteine therapy revealed a P value of 0.000 <α=0.05. The conclusion of this study is that there is an effect of high-dose intravenous N Acetylcysteine on Tumor Necrosis Factor-α, and there is a significant difference in the change in Tumor Necrosis Factor-α between the Intervention and control groups.